Analisis Pengaruh Efektivitas Mesin Self Check-In terhadap Kepuasan Penumpang di Bandar Udara Adi Soemarmo Surakarta - Agus Purwadi; Tarisa Dian Retno Sari; Ukkasyah Sabbit Aqdamana Lubis; Erwin Pasangkin (Politeknik Penerbangan Jayapura, 2024)
The self-check-in facility provides convenience for passengers, especially for those that do not bring excess baggage, by speeding up the process of entering the waiting area. Although passengers with baggage need to queue to drop off their luggage at the counter, the use of self-check-in machines overall accelerates the check-in process and reduces queues at the counter. This research used a quantitative method, involving two variables: effectiveness and satisfaction. Data collection was conducted by distributing questionnaires to 100 respondents, and the data were processed using SPSS 27 software. The results of research indicate that the use of self-check-in machines has a significant impact on passenger satisfaction, particularly in terms of time efficiency and convenience. The self check-in machines significantly influence passenger satisfaction at Adi Soemarmo Airport by 89.5%, with the remaining 10.5% influenced by variables not included in this research. These findings were expected to assist airport management in improving services and passenger satisfaction through the optimization of self check-in technology.